Avaliações de empresas de Tecnologia da Informação no Brasil que possuem ações na BMF & Bovespa no período de 2009 á 2014 - Oliveira, Eduardo Cezar de (2015)
This paper aims to present the various methods used to conduct the evaluation of the companies and carry out a comparison of the market value of the it companies that have shares in BMF Bovespa & with the present value of the cash flow calculated using the information from the financial annual reports had two stages. First, an exploratory study was conducted through literature search and on second, there was a market research using the main methodology: the present value of the discounted cash flow. For the calculations, has selected 10 information technology companies that have shares in BMF & Bovespa and performed the comparison between the present value of the discounted cash flow with their market value, which presented evidence that Brazilian investors still have insecurity in buying these papers compared the behavior of North American investors about North Americans companies